JAMINAN MUTU MANAJEMEN KEUANGAN BERBASIS AKUNTABILITAS DALAM PERSPEKTIF SYARIAH DI SEKOLAH - Andrianto, Andrianto (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2019)
This study aims to determine the practice of accountability-based quality assurance in theperspective of Islamic financial management at SMK Muhammadiyah 1 Kapasan-Surabaya.This research data is the result of observations in the field through interviews with 3informants, namely the principal, vice principal and treasurer. The theory used is Sharia'Enterprise Enterprise Theory (SET), the concept of accountability based on justice and honesty.The research approach used is a case study. This study uses the Yin analysis method to analyzequalitative data. The results showed that in the accountability of school financial managementthere are values of spirituality such as monotheism and caliph that influence the existence ofvertical accountability practices and horizontal accountability in schools both financialmanagement. Keywords: financial management accountability, the concept of accountability based onmonotheism and khalifah, sharia'te enterprise theory.